FORMATION OF SECONDARY NOMINATIVE UNITS IN DIFFERENT LANGUAGES AND THEIR UNIVERSALITY - Kiyаsоvа, Rа’nо (Журнал иностранных языков и лингвистики, 2023)
Our article examines the formation of secondary nominative units. Analysis shows that the first internal basis of nominative units is the observation of things and phenomena. External parties that directly determine the implementation of sustainable structural information reflect the important traditional mechanisms of each language. A similar meaning makes a difference in the meaning of languages. But the inner basis refers to the totality of rational tendencies in languages. To prove the points, we analyzed the received noun, which represents the noun of the agent in the word-formation system of English and Uzbek languages.